Customizing Early Intervention Treatment for Psychosis in the UTHealth - Harris County Psychiatric Center - Alia R Warner PhD; Gordon C Shen PhD, SM; Jane E Hamilton PhD, MPH, LCSW; Luca Lavagnino MD, PhD; Scott D Lane PhD (SAGE Publishing, 2021)
High-need, high-cost patients include those with diagnosed serious mental illnesses (e.g., schizophrenia; SMI). They often delay or fail to seek treatment. If they receive treatment, care is often sought from generalist settings (e.g., primary care or emergency medicine) or is suboptimal due to the provision of limited, non-evidence-based intervention and lack of communication, integration, and coordination among providers. This results in high aggregate costs and poor outcomes. Value-based health care requires care coordination to address the medical and social needs of this population. We describe a unique early intervention program for SMI that emanates from an inpatient setting: The Early Onset Treatment Program (EOTP) at the University of Texas Health Science Center at Houston-Harris County Psychiatric Center. The EOTP offers free, phase-specific, multidisciplinary treatment to young adults without health insurance with the aim of improving their long-term outcomes and reducing the rate of rehospitalization. An evaluation of the EOTP indicates program participants were significantly less likely to be rehospitalized at six months (4.73 times less likely) and at 12 months (3.5 times less likely) than a comparison group ( p <.001), and participants' scores of symptomatology and disability significantly decreased following treatment.